2006
DOI: 10.4049/jimmunol.177.5.3337
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IFN-α and Nitric Oxide in the Release of HMGB1 by RAW 264.7 Cells Stimulated with Polyinosinic-Polycytidylic Acid or Lipopolysaccharide

Abstract: High mobility group protein 1 (HMGB1) is a nonhistone nuclear protein with a dual function. Inside the cell, HMGB1 binds to DNA and modulates a variety of processes, including transcription. Outside the cell, HMGB1 displays cytokine activity and can promote inflammation, serving as a mediator in models of shock and arthritis. In in vitro studies, proinflammatory molecules such as LPS, lipoteichoic acid, dsRNA, TNF-α, and IFN-γ can induce HMGB1 release from macrophages. To define further the release process, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 51 publications
8
88
1
Order By: Relevance
“…In a previous study, we showed that NO and IFN-␣ differentially mediated the release of HMGB1 by LPS and poly(I:C) in a process that may depend on JNK activation (16). In these experiments, we showed that inhibiting iNOS or neutralizing IFN-␣ by an Ab reduced HMGB1 release.…”
Section: The Effects Of No Ifn-␣ and Jnk On Apoptosis And Hmgb1 Relmentioning
confidence: 66%
See 1 more Smart Citation
“…In a previous study, we showed that NO and IFN-␣ differentially mediated the release of HMGB1 by LPS and poly(I:C) in a process that may depend on JNK activation (16). In these experiments, we showed that inhibiting iNOS or neutralizing IFN-␣ by an Ab reduced HMGB1 release.…”
Section: The Effects Of No Ifn-␣ and Jnk On Apoptosis And Hmgb1 Relmentioning
confidence: 66%
“…In previous experiments, we showed that inhibiting JNK activation reduced extracellular release of HMGB1 induced by poly(I:C) or LPS (16). To evaluate the role of JNK in apoptosis induced by LPS or poly(I:C), we analyzed the effects of JNK inhibitor on caspase activities and LDH levels in RAW 264.7 cells stimulated with LPS or poly(I:C).…”
Section: Neutralizing Ifn-␣ Did Not Affect Hmgb1 Release Induced By Lmentioning
confidence: 99%
“…The level of HMGB1 was determined by Western blotting using anti-HMGB1 Abs, and quantified by densitometric scanning of the exposed x-ray film. Relative densitometric value of HMGB1 of each sample shown as arbitrary units in the figures was calculated by arbitrarily assigning that of control (a LPS (or Escherichia coli)-treated sample) as 1 (16).…”
Section: Measurement Of Cytokinesmentioning
confidence: 99%
“…B et al, 2004). Acteoside-induced HO-1 expression in Raw264.7 cells was significantly inhibited by Nrf2 siRNA, indicating the involvement of p38 MARK/Nrf2 signaling; however, others have produced compelling evidence for the lack of involvement of NFkB and p38 in HMGB1 release in LPS-treated macrophages, while emphasizing the role of Janus kinase 2/signal transducer and activator of transcription-1 and iNOS/ NO signaling in HMGB1 release (Jiang and Pisetsky, 2006;Oh et al, 2009). Thus, further study is needed to identify the pathways involved in the inhibition of HMGB1 downstream of HO-1.…”
Section: Discussionmentioning
confidence: 99%